Ectopic expression of two AREB/ABF orthologs increases drought tolerance in cotton (Gossypium hirsutum). (30th March 2017) - Kerr, Tyson C. C.; Abdel‐Mageed, Haggag; Aleman, Lorenzo; Lee, Joohyun; Payton, Paxton; Cryer, Dakota; Allen, Randy D.
Abstract: Plants have evolved complex molecular, cellular and physiological mechanisms to respond to environmental stressors. Because of the inherent complexity of this response, genetic manipulation to substantially improve water deficit tolerance, particularly in agricultural crops, has been largely unsuccessful, as the improvements are frequently accompanied by slower growth and delayed reproduction. Here, we ectopically express two abiotic stress‐responsive bZIP AREB/ABF transcription factor orthologs, Arabidopsis ABF3 and Gossypium hirsutum ABF2D, in G. hirsutum, to compare the effects of exogenous and endogenous AREB/ABF transgene overexpression on dehydration resilience. Our results show that ectopic expression of each of these orthologs increases dehydration resilience, although these increases are accompanied by slower growth. These phenotypic effects are proportional to the ectopic expression level in the GhABF2D transgenic plants, while the phenotypes of all of the AtABF3 transgenic plants are similar, largely independent of ectopic expression level, possibly indicating differential post‐transcriptional regulation of these transgenes. Our results indicate that overexpression of exogenous and endogenous ABF homologs in G. hirsutum substantially increases drought resilience, primarily through stomatal regulation, negatively impacting transpiration and photosynthetic productivity. Summary Statement: In order to understand the role of abscisic acid‐responsive transcription factors (ABFs) in the regulation of drought tolerance in cotton, we carried out a functional analysis of two genes that express representative ABFs from Arabidopsis and cotton. These genes were ectopically expressed in transgenic cotton plants, and the drought tolerance phenotypes of these plants were analysed. Our results demonstrate that ectopic expression of ABFs from either Arabidopsis or cotton lead to increased stress tolerance mediated primarily through reduced transpirational water loss. The potential uses of ABF transgenes to improve cotton drought tolerance are discussed.